Decreasing Trend in Formaldehyde Detected From 20‐Year Record at Wollongong, Southeast Australia. Issue 14 (24th July 2019) - Lieschke, Kaitlyn J.; Fisher, Jenny A.; Paton‐Walsh, Clare; Jones, Nicholas B.; Greenslade, Jesse W.; Burden, Sandy; Griffith, David W. T.
Abstract: The response of atmospheric composition to ongoing environmental change remains poorly constrained across much of the Southern Hemisphere. We use a 20‐year record of ground‐based total column measurements from Wollongong, southeast Australia to identify a statistically significant decreasing trend in formaldehyde of −1.9 [−2.2, −1.7]%/year. The trend is consistently negative across all months except November. Satellite data indicate that the trend at Wollongong is distinctly local and is superimposed on a regional‐scale increase likely driven by changes in methane. In austral summer, coincident changes in hydrogen cyanide suggest that decreases in local biomass burning can only partly explain the observed trend. In the absence of other explanations, we infer that the observed formaldehyde trend is likely driven by decreasing industrial emissions. In November, an observed increasing temperature trend is consistent with an earlier onset of biogenic emissions in the region, driving increased biogenic formaldehyde that counteracts the overall decrease. Key Points: Significant decrease in HCHO from 1996 to 2015 is observed at Wollongong in all months but November, superimposed on a regional HCHO increase Decrease is linked to changes in summer biomass burning and declining local industrial emissions Lack of trend in November is linked to rising temperature and earlier onset of biogenic emissions